2019
DOI: 10.1016/j.ajpath.2019.02.012
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Combination of Prion Strain Co-Occurrence in Patients with Sporadic Creutzfeldt-Jakob Disease

Abstract: Six subgroups of sporadic Creutzfeldt-Jakob disease have been identified by distinctive clinicopathologic features, genotype at polymorphic codon 129 [methionine (M)/valine (V)] of the PRNP gene, and type of abnormal prion proteins (type 1 or 2). In addition to the pure subgroups, mixed neuropathologic features and the coexistence of two types of abnormal prion proteins in the same patient also have been reported. Here, we found that a portion of the patients previously diagnosed as MM1 had neuropathologic cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…However, we consider OD, the most important neuropathological finding for the diagnosis of the disease. Relatively severe neuronal loss in the medial thalamus is also seen in the brains of patients with sCJD-MM1 after a long-term illness (>15 months), while the number of neurons in the inferior olive or the lateral thalamus is largely preserved irrespectively of the disease duration ( Kobayashi et al , 2019 a ). Accordingly, Kobayashi et al have recently reported that, in cases of sCJD-MM1 with MM2T pathology, neuronal loss in the inferior olivary nucleus rather than in the medial thalamus is more specific for FFI or sFI.…”
Section: Discussionmentioning
confidence: 99%
“…However, we consider OD, the most important neuropathological finding for the diagnosis of the disease. Relatively severe neuronal loss in the medial thalamus is also seen in the brains of patients with sCJD-MM1 after a long-term illness (>15 months), while the number of neurons in the inferior olive or the lateral thalamus is largely preserved irrespectively of the disease duration ( Kobayashi et al , 2019 a ). Accordingly, Kobayashi et al have recently reported that, in cases of sCJD-MM1 with MM2T pathology, neuronal loss in the inferior olivary nucleus rather than in the medial thalamus is more specific for FFI or sFI.…”
Section: Discussionmentioning
confidence: 99%
“…One of the frequently advanced explanations is that prions are constituted of a cloud of substrains or a “quasi-species” [7] and when confronted with transmission barrier, the fittest substrain will emerge. Combinations of substrains in varying concentration have been found to co-replicate in the same brain, and their isolation and thus their phenotypic expression has been possible because of i) different tropism for the lymphoid tissue [8], ii) different capacity to adapt on cross-species transmission [77], iii) different capacities to accommodate different PrP C levels [78] or PrP gene polymorphism [79]. Co-replication of structurally distinct assemblies such as those isolated by fractionation methods is more difficult to identify, as no obvious phenotypic differences have been noticed on the transmission of the isolated assemblies [24,25].…”
Section: Time To Revisit the Molecular Basis Of The Prion Replicatmentioning
confidence: 99%
“…28 Recent studies demonstrated that the coexistence of more than one PrP Sc strain in a single patient ("mixed" case) is a frequent finding in CJD, and that, in particular, virtually all sCJD patients with type 2 PrP Sc also have type 1 PrP Sc . 17,22,23,25,29,30 Clinicopathological phenotypes of patients are mainly determined by the predominant type of strain. 17,23,29,30 The transmissible properties of strains M2C and M2T are different.…”
Section: Discussionmentioning
confidence: 99%
“…17,22,23,25,29,30 Clinicopathological phenotypes of patients are mainly determined by the predominant type of strain. 17,23,29,30 The transmissible properties of strains M2C and M2T are different. 22,25,30 The cooccurrence of both strains seen in our patient is, therefore, not considered to represent the presence of a transitional form but the cooccurrence or coinfection of different strains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation